Peran Brand Ambassador dalam Meningkatkan Brand Awareness pada Produk Shampoo Pantene - Rizkya Hantoro, Naditha; Yulianita, Neni (CV. Creative Tugu Pena, 2023)
The focus of this research is to analyze the role of brand ambassadors in building brand awareness on YouTube Pantene Indonesia ads, especially on Pantene shampoo products. This research seeks to understand the contribution made by the brand ambassador, namely KeanuAGL, in increasing consumer awareness of the Pantene brand through advertisements displayed on the YouTube platform. Researchers used qualitative research methods with a case study approach. Data collection was carried out through several techniques, including in-depth interviews with research subjects, namely KeanuAGL fans who are the target audience for Pantene advertisements, observation of advertisements on the YouTube platform involving KeanuAGL brand ambassadors, literature studies, and online data searches to obtain information related to the subject. study. The results of the study show that the role of brand ambassador KeanuAGL in Pantene Indonesia YouTube ads plays an important role in building brand awareness. His presence provides a positive association between the Pantene brand and KeanuAGL's popularity and influence as a well-known celebrity and influencer. KeanuAGL effectively represents the Pantene brand by communicating the values and benefits of its products to the target audience. Keywords: Marketing Communications, Brand Ambassador, Brand Awareness, Advertising